The effect of proactive, interactive, two-way texting on 12-month retention in antiretroviral therapy: Findings from a quasi-experimental study in Lilongwe, Malawi. - Caryl Feldacker; Robin E Klabbers; Jacqueline Huwa; Christine Kiruthu-Kamamia; Agness Thawani; Petros Tembo; Joseph Chintedza; Geldert Chiwaya; Aubrey Kudzala; Pachawo Bisani; Dumisani Ndhlovu; Johnnie Seyani; et al. (PLoS ONE)
Background Retaining clients on antiretroviral therapy (ART) is challenging, especially during the first year on ART. Mobile health (mHealth) interventions show promise to close retention gaps. We aimed to assess reach (who received the intervention?) and effectiveness (did it work?) of a hybrid two-way texting (2wT) intervention to improve ART retention at a large public clinic in Lilongwe, Malawi. Methods Between August 2021-June 2023, in a quasi-experimental study, outcomes were compared between two cohorts of new ART clients: 1) those opting into 2wT who received automated, weekly motivation short messaging service (SMS) messages and response-requested appointment reminders; and 2) a matched historical cohort receiving standard of care (SoC). Reach was defined as "the proportion clients ≤6 months of ART initiation eligible for 2wT". 2wT effectiveness was assessed in time-to-event analysis. Retention was presented in a Kaplan-Meier plot and compared between 2wT and SoC using a log-rank test. The effect of 2wT on ART dropout (lost to follow-up or stopped ART) was estimated using Fine-Gray competing risk regression models, adjusting for sex, age and WHO HIV stage at ART initiation. Results Of 1,146 clients screened, 501 were eligible for 2wT, a reach of 44%. Lack of phone (393/645; 61%) and illiteracy (149/645; 23%) were the most common ineligibility reasons. Among 468 participants exposed to 2wT, 12-month probability of ART retention was 91% (95% CI: 88% - 94%) compared to 76% (95% CI: 72% - 80%) among 468 SoC participants (p<0.001). Compared to SoC, 2wT participants had a 65% lower hazard of ART dropout at any timepoint (sub-distribution hazard ratio 0.35, 95% CI: 0.24-0.51; p<0.001). Conclusions 2wT did not reach all clients. For those who opted-in, 2wT significantly increased 12-month ART retention. Expansion of 2wT as a complement to other retention interventions should be considered in other low-resource, routine ART settings.